Kandungan Pestisida Organoklorin dalam Air Susu Ibu di Daerah Pertanian Bawang Merah Kabupaten Brebes - Cahyaningrum, Dwi; Denny, Hanifa Maher; Adi, M. Sakundarno (Jurnal Promosi Kesehatan Indonesia, 2018)
Background: Organochlorine pesticides were widely used in agricultural at the past, these compounds are persistent in the environment and can be bioaccumulate and biomagnificate in food chain. Prenatal organochlorine exposure may lead to premature birth, spontaneous abortion and infere central nervous system function. Women living in agriculture area pose high risk of pesticides exposure resulting from their agriculture occupation and environment exposure. Breast milk could be a suitable matrix for monitoring organochlorine exposure in human. This study aimed to assess the content of organochlorine pesticides in human breast milk, women involvement in agricultural activity and factors related to the level of organochlorine compounds in breast milk.Method: The qualitative descriptive method using cross sectional approach was applied in this research. There were 14 partisipants.Results: The result demonstrated that 4 partisipans had p’pDDE level above 0,01 mg/kg (0,018-1,082), and 11 partisipans had level of Dieldrin below 0,01 mg/kg (0,001-0,007). Concentration p’pDDE tend to decreased as the increased of parity, level of knowledge, and level practices of pesticide. Dietary habits especially fish consumption was considered as a source of organochlorine exposure to human. Supervision policy the used of pesticide hasn’t effective yet to increase safe practices of pesticides among farmers.Keywords : Organochlorine, breast milk, safe practices of pesticides